Snow crystals natural and artificial - Nakaya, Ukichirō 1900-1962 (Harvard Univ. Press, 1954)
Work at Dept. of Physics, Hokkaido University, Japan. Comprehensive work on the nature of snow. Different shapes of snow crystals are described and classified.